Towards an understanding of the avian virome - François, S; Pybus, OG (Microbiology Society, 2020)
The last two decades have seen the rise of viromics, the study of viral communities through the detection and characterization of virus genome sequences. Here we systematically review and summarize the scope and limitations of our current understanding of avian viromes, in both domesticated and wild-bird populations. We compare this viromic work to the broader literature on avian prokaryotic microbiomes, and highlight the growing importance of structured sampling and experimental design for testing explanatory hypotheses. We provide a number of recommendations for sample collection and preliminary data analysis to guide the development of avian viromics. Avian viromes have the potential to inform disease surveillance in poultry and improve our understanding of the risk of zoonotic viruses to human health.